1990
DOI: 10.1128/jcm.28.5.876-881.1990
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic karyotyping of typical and atypical Candida albicans

Abstract: Electrophoretic karyotypes of atypical isolates of Candida albicans, e.g., strains that were germ tube negative, failed to express proteinase activity, demonstrated low virulence for mice, formed hyperchlamydoconidia, produced hyperhyphae, or were sucrose negative (including the type strain of Candida stellatoidea), were compared with those of typical C. albicans. Karyotypes of whole-cell DNA of classical C. albicans examined with transverse alternating-field electrophoresis under specific conditions were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…[5][6][7][8][9] Our results are in good agreement with those reported in previous studies on PFGE typing of C. albicans where the karyotype pattern consists mainly of six or seven bands, but more rarely eight bands. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Differences in the patterns obtained may be related to technical variations in PFGE technique used. [7][8][9][10]17 It is important to point out that the number of bands revealed by PFGE does not necessarily correspond to the number of the yeast chromosomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[5][6][7][8][9] Our results are in good agreement with those reported in previous studies on PFGE typing of C. albicans where the karyotype pattern consists mainly of six or seven bands, but more rarely eight bands. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Differences in the patterns obtained may be related to technical variations in PFGE technique used. [7][8][9][10]17 It is important to point out that the number of bands revealed by PFGE does not necessarily correspond to the number of the yeast chromosomes.…”
Section: Discussionsupporting
confidence: 92%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Differences in the patterns obtained may be related to technical variations in PFGE technique used. [7][8][9][10]17 It is important to point out that the number of bands revealed by PFGE does not necessarily correspond to the number of the yeast chromosomes. Indeed, homologous chromosomes may migrate separately possibly because of deletion, translocation, insertion of movable DNA or differences in the amount or distribution of repetitive sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Pheno-or genotypically atypical C. albicans isolates have also been described in previous studies. Mahrous et al (26) found distinct karyotypes among atypical C. albicans isolates (isolates that had at least one of the following characteristics: germ-tube negative, saccharose-negative, no proteinase activity, low virulence for mice, formation of hyperchlamydocinidia or hyperhyphae) compared to karyotypes of typical C. albicans isolates. McCullough et al (28) found that some phenotypically normal C. albicans isolates from HIVinfected subjects did not hybridize to a species-specific probe and exhibited higher extracellular proteinase activity, greater adherence to buccal epithelial cells and lower susceptibity to 5-flucytosine than the typical C. albicans isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, most of the characterization of Candida spp. has been concentrated on C. albicans (Iwaguchi et al 1990;Mahrous et al 1990;Magee et al 1992). Recently, two © 1999 The Society for Applied Microbiology, Journal of Applied Microbiology 87, 29-40 groups of workers (Carlotti et al 1994(Carlotti et al , 1996(Carlotti et al , 1997aManavathu et al 1996) have used variations of molecular methods for typing of clinical strains of C. krusei.…”
Section: Introductionmentioning
confidence: 99%